Pengaruh Pengetahuan Investasi, Analisis Risiko, Modal Minimal, dan Motivasi Investasi Terhadap Minat Berinvestasi Mahasiswa Melalui Galeri Investasi Syariah - Irma Rahmawani Panjaitan; Sri Ramadhani (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to examine and analyze how the relationship between investment knowledge, risk analysis, minimum capital, and investment motivation on students' interest in investing through Islamic investment galleries. This research was conducted using a quantitative method with a sample of 68 respondents taken from students of the State Islamic University of North Sumatra. Data analysis techniques were carried out through validity, reliability, normality tests, multiple regression analysis tests, coefficient of determination tests, and hypothesis testing F and t. The research results obtained showed that there was influence from investment knowledge and investment motivation variables, but other variables, namely risk analysis and minimum capital, did not affect investment interest in undergraduate students of the Faculty of Economics and Islamic Business, State Islamic University of North Sumatra. The most dominant investment motivation for students' interest in investing is through Islamic investment galleries